PEMIKIRAN FIQH WANITA QOSIM AMIN (Jurnal Studi Gender Indonesia, 2013)
This paper explores Qasim Aminâs thinking on fiqh related to women; hijab, divorce, and polygamy.Initially, Qasim Amin wrote al-Mis} riyyu>Â  n to defend the patriarchal traditions that occurred in Egyptwhich is criticized by DâCouhourt. But, in five years later he wrote the book Tah}Â  ri> r marâah that reconstructsfiqin (Islamic jurisprudence) on womenâs issues. He reinforced his opinion in his later piece ofÂ  writing titledal-marâah al-jadidah. There are several factors behind his shifting way of thinking; the influence ofmodernization in Egypt and the influence ofÂ  French culture where he was studying. In social science theory,changing way ofÂ  thinking is reasoneable and is in accordance with the theory ofÂ  creative personality initiatedby David Mc.Celland.